Absolute configuration of iminimycin B, a new indolizidine alkaloid, from Streptomyces griseus OS-3601. Issue 30 (27th July 2016) - Nakashima, Takuji; Miyano, Rei; Matsuo, Hirotaka; Iwatsuki, Masato; Shirahata, Tatsuya; Kobayashi, Yoshinori; Shiomi, Kazuro; Petersson, George A.; Takahashi, Yōko; Ōmura, Satoshi
Graphical abstract: Highlights: Iminimycin B was discovered from Streptomyces griseus OS-3601 by a physicochemical screening. Structure of iminimycin B was a unique novel pyridinium alkaloid. Absolute configuration of iminimycin B was determined by NMR, eECD analysis, and Marfey's method. Abstract: Iminimycin B, a novel indolizine alkaloid featuring a rare pyridinium, was isolated from the cultured broth of a streptomycin-producing strain, Streptomyces griseus OS-3601, through a physicochemical screening method. Its structure was elucidated on the basis of mass and NMR analyses. Stereochemical assignment of iminimycin B was archived by NMR studies, electronic circular dichroism (ECD) analysis, and advanced Marfey's method.